EMERGING AS A TEACHER (Editors: Robert V. Bullough, Jr., J. Gary Knowles, and Nedra A. Crow) - Russell, Tom (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1993)
Robert V. Bullough, Jr., J. Gary Knowles, and Nedra A. Crow (Editors). EMERGING AS A TEACHER New York: Routledge, Chapman & Hall, 1992. 114 pp. 62.50 (Can.) and 49.95 (U.S.) for cloth, 15.95 (U.S.) for paper